2019
DOI: 10.1186/s12864-018-5422-2
|View full text |Cite
|
Sign up to set email alerts
|

Identification and analysis of long non-coding RNAs in response to H5N1 influenza viruses in duck (Anas platyrhynchos)

Abstract: BackgroundLong non-coding RNAs (lncRNAs) are important component of mammalian genomes, where their numbers are even larger than that of protein-coding genes. For example, human (Homo sapiens) (96,308 vs. 20,376) and mouse (Mus musculus) (87,774 vs. 22,630) have more lncRNA genes than protein-coding genes in the NONCODEv5 database. Recently, mammalian lncRNAs were reported to play critical roles in immune response to influenza A virus infections. Such observation inspired us to identify lncRNAs related to immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 36 publications
(43 reference statements)
3
4
0
Order By: Relevance
“…Accumulated studies demonstrated that viral infection can alter lncRNA expression profile of host (44), including infectious bronchitis virus infection of primary dendritic cells (45), H5N1 influenza viruses infection of ducks (46), and Porcine reproductive and respiratory syndrome virus infection of endometrial epithelial cells (47). In our study, the change of lncRNA expression profile was also observed in DEFs in response to DTMUV infection.…”
Section: Discussionsupporting
confidence: 70%
“…Accumulated studies demonstrated that viral infection can alter lncRNA expression profile of host (44), including infectious bronchitis virus infection of primary dendritic cells (45), H5N1 influenza viruses infection of ducks (46), and Porcine reproductive and respiratory syndrome virus infection of endometrial epithelial cells (47). In our study, the change of lncRNA expression profile was also observed in DEFs in response to DTMUV infection.…”
Section: Discussionsupporting
confidence: 70%
“…The majority of lncRNAs in the liver and adrenal glands is located in intergenic regions, which is consistent with previous studies performed in other mammalian [ 49 , 50 ], plant [ 51 , 52 ] and fungal [ 53 , 54 ] species. In addition, previous research showed that animal lncRNAs are shorter and have fewer exons than PCGs [ 55 , 56 ], which is in line with our findings (Fig. 3 b and c).…”
Section: Discussionsupporting
confidence: 93%
“…In human cells, a long noncoding RNA (lncRNA) Lnczc3h7a also contributes to stabilizing the interaction between TRIM25 and RIG-I CARD domains (Lin et al, 2019). Recently, duck lncRNA were analyzed during HPAI and LPAI infection to determine which were differentially expressed and potentially involved in influenza A control (Lu et al, 2019). This study did not assess whether lnczc3h7a is differentially expressed, nor is it known if duck lnczc3h7a can function in the same manner, but this augmentation by lncRNAs may well be conserved.…”
Section: Trim25mentioning
confidence: 99%